Educational Orders as a Form of Implementation Diversion Programs – Critical Review - Jovanović, Vladimir; Ivanović, Angelina (Zbornik Instituta za kriminološka i sociološka istraživanja, 2020)
The aim of the paper is the analysis and presentation of diversion programs, clarification of what they represent, with reference to the comparative burst and emphasis on a critical review of both positive and negative aspects of diversion programs. The subject of the paper, consequently, is the analysis of the application of educational orders as a form of diversionary programs, the forms in which they are implemented and what makes the positive and what the negative aspects of educational orders. The authors in the text try to present the methods of content analysis and in a short part of the comparative analysis to present the theoretical basis and practical motives for establishing programs of this kind in practice. They make a well-founded conclusion about the theoretical basis of implementation practice in the Republic of Serbia and give an overview of the Law on Juvenile Delinquents and Criminal Protection of Juveniles, with an attempt to identify the purpose and motives for its establishment. In addition, they give their view of the positive and negative sides of these programs, which is based on the analysis of the content of various available professional and scientific content.